Tumefactive demyelinating disease with isolated spinal cord involvement. Issue 5 (20th June 2014) - Makary, Mina S; Kirsch, Claudia F
Tumefactive multiple sclerosis (TMS) is an unusual variant of demyelinating disease. TMS has a variable and unknown progression and presents with features similar to a neoplasm making the determination a diagnostic challenge to clinicians. This report presents one of the very few reported cases of isolated spinal cord TMS, and the second case to describe TMS of the lower spinal cord, given that the lesions are typically cervical. This case study presents a diagnostic approach based on clinical, laboratory, and imaging characteristics, as well as sheds some light on the response to therapy and disease evolution.